Effects of PPARG and PPARGC1A gene polymorphisms on obesity markers - Muntean, Carmen; Sasaran, Maria Oana; Crisan, Adriana; Banescu, Claudia (Frontiers in Public Health, 2022)
Pediatric obesity presents a multifactorial etiology, which involves genetic traits as well, including single nucleotide polymorphisms. The aim of the study is to investigate the contribution of PPARG gene polymorphisms (namely Pro12Ala rs1801282, His447His rs3856806, and Pro115Gln rs1800571) and PPARGC1A rs8192678 SNP on the anthropometric and metabolic parameters in a population of Romanian children. We conducted a cross-sectional study of 295 Caucasian children, divided according to the body mass index (BMI) z-score into the study (obese and overweight) group of 130 children and the control (normoponderal) group of 165 children. Anthropometric parameters were greater in the obese and overweight population as opposed to controls, with significant differences (p<0.01) found for the weight (2.77±1.54 SD vs -0.04±1.15 SD), body mass index (BMI) (2.28±0.97 SD vs -0.18±1.19 SD), mid-upper arm circumference (MUAC) (4.59±2.28 SD vs 0.28±3.45 SD), tricipital skin-fold (TSF) (3.31±3.09 SD vs 0.62±7.28 SD) and waist-to-height ratio (WHtR) (0.61±1.51 SD vs -0.35±1.35 SD) z-scores. Moreover, triglyceride values were higher in the study group (118.70±71.99 SD vs 77.09±37.39 SD). No significant difference in the allele and genotype distribution of investigates gene polymorphisms was observed between the studied groups (p>0.05). PPARG (rs1801282, rs3856806, rs1800571) were not associated with demographic, anthropometric, and laboratory parameters. However, PPARGC1A rs8192678 CC genotype was associated with TSF z-score (p=0.03), whereas total and LDL cholesterol levels were significantly higher among TT homozygotes (p<0.01). Our data suggest that PPARG (rs1801282, rs3856806, rs1800571) and PPARGC1A (rs8192678) gene polymorphisms were not associated with childhood and adolescence overweight and obesity. The present study identified a significant increase in fasting glucose levels, triglyceride, albumin, and ALT levels in children with excess weight, as well as expected important upward variation of anthropometric parameters (BMI, MUAC, TSF z-scores).